Role of STAT3 in Transformation and Drug Resistance in CML - Nair, Rajesh R.; Tolentino, Joel H.; Hazlehurst, Lori A. (Frontiers in Oncology, 2012)
Chronic Myeloid Leukemia (CML) is initially driven by the bcr-abl fusion oncoprotein. The identification of bcr-abl led to the discovery and rapid translation into the clinic of bcr-abl kinase inhibitors. Although, bcr-abl inhibitors are efficacious, experimental evidence indicates that targeting bcr-abl is not sufficient for elimination of minimal residual disease found within the bone marrow (BM). Experimental evidence indicates that the failure to eliminate the leukemic stem cell contributes to persistent minimal residual disease. Thus curative strategies will likely need to focus on strategies where bcr-abl inhibitors are given in combination with agents that specifically target the leukemic stem cell or the leukemic stem cell niche. One potential target to be exploited is the JAK/STAT3 pathway. Recently using STAT3 conditional knock-out mice it was shown that STAT3 is critical for initiating the disease. Interestingly, in the absence of treatment, STAT3 was not shown to be required for maintenance of the disease, suggesting that STAT3 is required only in the tumor initiating stem cell population (Hoelbl et al., 2010). In the context of the BM microenvironment, STAT3 is activated in a bcr-abl independent manner by the cytokine milieu. Activation of JAK/STAT3 was shown to contribute to cell survival even in the event of complete inhibition of bcr-abl activity within the BM compartment. Taken together, these studies suggest that JAK/STAT3 is an attractive therapeutic target for developing strategies for targeting the JAK-STAT3 pathway in combination with bcr-abl kinase inhibitors and may represent a viable strategy for eliminating or reducing minimal residual disease located in the bone marrow in CML.